Biochemical, nutraceutical and phytochemical characterization of chia and basil seeds: A comparative study. Issue 1 (31st December 2023) - Khursheed, Tabeen; Fatima, Tabasum; Qadri, Tahiya; Rafiq, Asima; Malik, Ajaz; Naseer, Bazila; Hussain, Syed Zameer
ABSTRACT: Chia and basil seeds have comparable nutritional profiles, bioactive components, and phytochemistry, which make it difficult for consumers and researchers to choose between the two. Thus, an in-depth study was conducted to compare the physiochemical, nutritional and bioactive profile of these seeds in order to obtain complete database regarding nutritional and phytochemical profiling of both seeds. The wonder seeds were analyzed for physico-chemical composition, fatty acid constituents, amino-acid profile and phytochemical screening. Fatty acid constituents were determined using GC-MS, while amino acids profile and identification and quantification of phytochemicals were performed using HPLC procedure. Physico-chemical evaluation of basil and chia seed revealed that basil was found superior to chia in terms of dietary fiber (40.85 g/100 g), fat content (33.10 g/100 g), vitamin A (1583 µg/100 g) and E (779 µg/100 g) while chia seed was rich in protein (21.54 g/100 g), iron (7.7mg/100 g), magnesium (335 mg/100 g) and phosphorus (860 mg/100 g). Amino acid profiling revealed the presence of high-quality protein in chia seeds comprising of almost all essential and non-essential amino acids in significant (p < .05) amounts as compared to basil seeds. Furthermore, higher proportion of α-linoleic acid (ALA) was detected in basil seeds (24.4g/100 g) as compared to chia seeds (5.25 g/100 g) as determined by GC-MS. Phytochemical screening showed that basil contained significantly (p < .05) higher amounts of total phenolic (17.66mgGAE/g of dry sample) and flavonoid content (0.57mgQE/100 g of dry sample) in comparison to chia seeds, which contributed to its higher anti-oxidant activity. Phenolic characterization revealed that basil seeds contained higher concentration of caffeic acid (4780.01 µg/g) followed by gallic acid (2330 µg/g). The inference drawn from the study concludes that both seeds can be put forth for enrichment of various food items or can be directly consumed as functional foods.